Aktivitas Antioksidan dan Kemampuan Proteksi terhadap Kerusakan DNA dari Protein Isolat Biji Melinjo (Gnetum Gnemon L.) Terhidrolisis Menggunakan Alkalase Terimobilisasi (Antioxidant Activity and Protection Ability Against DNA Damage of Isolate Protein Me - Anandini Aulia Safiera; Endah Puspitasari; Tri Agus Siswoyo (UPT Percetakan dan Penerbitan Universitas Jember, 2017)
Hydrolyzed protein isolates of melinjo seed using free alcalase has been known to have antioxidant potential. However, free alcalase can only be used once. Enzymes immobilization technique with entrapment method would overcome this problem. The immobilized enzyme characteristic was observed by SEM and hydrolysis degree value. The success of hydrolysis process was observed by SDS-PAGE. Antioxidant activity test was determined by the ability to inhibit hydroxyl radical and protection against DNA damage in 1% agarose gel. The result showed that protein isolates from melinjo seed had been successfully hydrolyzed by immobilized alcalase. Following hydrolysis showed that immobilized alcalase was effective to hydrolyze protein up to four times. Based on hydroxyl radical reduction activity test, antioxidant activity of hydrolyzed protein using immobilized alcalase had the same as that of glutathione as positive control antioxidant activity. In addition, hydrolyzed protein using immobilized alcalase had the ability toprotect DNA damage which showed by reversible change of supercoil band. Keywords: melinjo seed, hydrolyzed protein, immobilized alcalase, antioxidant